Factors that Affect Employee Engagement in The Workplace - Luthfi, Tengku Wildan; Putri, Vini Wiratno (Universitas Negeri Semarang, 2021)
This research aims to determine the effect of servant leadership and work motivation on employee engagement through job satisfaction on employees as a mediating variable of organization. The data was collected using an online questionnaire via google form method. The population in this study are employees of PT. BPR Surya Yudhakencana Banjarnegara Head Office as many as 80 employees. The sampling technique used in this research is using a saturated sample technique by taking the whole entire population of 80 respondents. Meanwhile, the data analysis method is using the Structural Equation Model-Partial Least Square (SEM-PLS) with the SmartPLS version 3.0 analysis tool. The results showed that service leadership had a significant effect on employee engagement and job satisfaction. However, work motivation is not significant to employee engagement and has a significant effect on job satisfaction. In addition, the effect of job satisfaction is able to mediate the effect of the relationship between servant leadership and work motivation on employee engagement. Suggestions for employees of organization is be brave to convey and sounds the aspirations to the company according to relevant procedures and also establishing a good relationships with leaders and co-workers. Furthermore, organization provide an adequate work facility, then provide bonuses for high-performing employees, and increase the employee salaries according to regulations and conducting promotions.